Full Table of Contents - Braude, Stephen (Journal of Scientific Exploration, 2010)
Editorial Stephen E. Braude Research Articles Anomalous Magnetic Field Activity During a Bioenergy Healing Experiment Margaret M. Moga, William F. Bengston Further Evidence of the Possibility of Exploiting Anticipatory Physiological Signals To Assist Implicit Intuition of Random Events Patrizio E. Tressoldi, Massimiliano Martinelli, Laura Scartezzini, Stefano Massaccesi Fire in Copenhagen and Stockholm. Indridason’s and Swedenborg’s “Remote Viewing” Experiences Erlendur Haraldsson, Johan L. F. Gerding Soal’s Target Digits: Statistical Links Back to the Source He Reported After All Roderick Garton Common Paranormal Belief Dimensions Neil Dagnall, Andrew Parker, Gary Munley, Kenneth Drinkwater Historical Perspective The 1907 Psychokinetic Experiments of Professor Filippo Bottazzi Antonio Giuditta Reviews Henry H. Bauer, Stephen Ray Flora, Tana Dineen, Michael Schmicker, Ephraim Fischbach, Carlos S. Alvarado, Renaud Evrard, Adrian Parker, Hale Brownlee Letter to the Editor Frank Pollard